The Effectiveness of the Student Executive Board Management of FITK UIN-SU in Developing the Personality Competence of Prospective Islamic Education Teachers - Fery Fadli; Mahariah Mahariah (Journal of General Education and Humanities, 2025)
This study evaluates the effectiveness of the Student Executive Board (DEMA) of the Faculty of Tarbiyah and Teacher Training (FITK) at UIN North Sumatra in developing the personality competence of prospective Islamic Religious Education (PAI) teachers. Personality competence is considered a fundamental aspect of professional educators, requiring intellectual capacity and moral and ethical maturity. A descriptive qualitative approach was employed, with data collected through interviews, participatory observation, and documentation. Findings indicate that DEMA substantially strengthens students’ discipline, social responsibility, and integrity. Active participation in organisational programs provides opportunities for internalising leadership values, social learning, and Islamic character building. Despite structural and cultural challenges, DEMA is a non-formal pedagogical arena that complements classroom learning and supports holistic personality development. The study suggests enhancing collaboration between student organisations and faculty management to optimise organisational roles in preparing competent PAI teachers with strong professional and personal qualities.